Penerapan Model Pembelajaran inquiry Dalam Meningkatkan Hasil Belajar Perserta Didik Pada pokok bahasan Pengukuran Di Kelas VII SMP Negeri 6 Halmahera Selatan - Jannah, Wahyuni M. (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2023)
Application of the inquiry learning model in improving student learning outcomes in the concept of measurement in class VII SMP Negeri 6 South Halmahera under the guidance of Mrs. Susi and Mrs. Kartini Lana. Physics Education Study Program at Kie Raha High School of Teaching and Education Ternate This research aims to improve the learning outcomes of students in Class VII of SMP Negeri 6 Halmahera Selatan through the application of an inquiry learning model. The research model used is qualitative with the research being carried out at SMP Negeri 6 Halmahera South, totaling 18 students. Sources of data sources come from teachers and students. Research data collection techniques were carried out using observer sheets implemented learning models and test questions. The data obtained were analyzed descriptively qualitatively. Based on the results of class VII action research at SMP Negeri 6 Halmahera Selatan which was carried out and produced, namely the results obtained by students in cycle 1 showed an increase compared to before being given learning by applying the inquiry learning model to the subject of measurement. After learning using the learning model the results increased from 57% to 75% in cycle II student learning outcomes using the subject measurement learning model showed an increase of 5.55% with an average value reaching 99.5%